Exploration of Banyuwangi Community's Perspective on Traditional Rituals In Decision Making Treatment Methods - Roziqin, Faldy Choirur Roziqin; Novita Surya Putri; Dwi Intan Septyani; Muhamad Fuad Hasyim; Nofia Erika Putri; Putri Widya Pramitha (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: The perspective phenomenon of the Banyuwangi community about the rituals of sanctity in disease has made the Banyuwangi people prefer alternative treatment rather than medical treatment. Objective: This study aims to explore the perspective of the Banyuwangi community on the rituals of sanctity in the decision-making of treatment methods. Method: Design research using qualitative with a phenomenological approach. Using the snowball sampling technique, 5 participants are patients undergoing supernatural and medical treatment. Data collection was done with semi-structured interviews. Data analysis using the Colaizzi method with the help of NVIVO Software 12. Result: Analysed 5 themes and 12 subthemes from the participants; 5 themes 1) Perceived susceptibility; 2) Perceived severity; 3) Cues to action; 4) Perceived benefit; 5) Perceived barriers. The perspective of the Banyuwangi community towards the ritual of santet in the decision-making of treatment methods is in line with the Health Belief Model theory belief construction. It positively affects the bio-psycho-social-spiritual aspect and boosts the immune system, which would not happen if the individual did not believe in his treatment. Recommendation: Recomendation for further research could be to further deepen the community's perspective on witchcraft which can influence the choice of treatment between medical and traditional supernatural. The impact of this research on society can provide information related to the concept of health and illness, such as spiritual and emotional health and how to overcome health problems experienced by society